DIRECTIONS FOR INCREASING THE INVESTMENT ACTIVITY OF INSTITUTIONAL STRUCTURES OF THE STOCK MARKET - Usmonov Zokirjon; Butayev Javlonbek (American Journals, 2025)
In this article, the activity of the stock market and institutional structures in it is analyzed, a number of theoretical materials and directions of activity of local stock market participants are reflected within this topic, and a number of recommendations are proposed.
Keywords: Investment, stock market, institutional structures, joint-stock company, IPO, commercial banks.